The Effect of Compensation and Work Environment on Employee Performance With Job Satisfaction As an Intervening Variable - Jimmy Fernando; Yossinomita Yossinomita; Paskalina Widiastuti Ratnaningsih (Universitas Muhammadiyah Sorong, 2026)
This research aims to examine the impact of compensation and work environment on employee performance at PT. Jambi Mandiri Sentosa, while assessing job satisfaction as a mediating variable, a study prompted by the company's fluctuating sales and downward performance trends. Using a quantitative approach and a census sampling strategy involving all 60 employees, data were analyzed through the PLS-SEM method using SmartPLS software. The findings reveal that while compensation and work environment have a positive and significant direct effect on both employee performance and job satisfaction, job satisfaction itself does not have a statistically significant impact on employee performance (P-Value 0.174 > 0.05). Consequently, the mediation analysis demonstrates that job satisfaction does not act as an intermediary between the independent variables and performance. It is concluded that the influence of compensation and work environment on productivity is primarily direct; therefore, management is advised to prioritize optimizing the work environment and fair compensation systems to ensure sales stability and operational efficiency, rather than relying on job satisfaction as a primary driver of performance.